2006
DOI: 10.1007/s00267-005-0014-8
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Influence of Natural Science in Regional-Scale Restoration Projects

Abstract: Regional-scale restoration is a tool of growing importance in environmental management, and the number, scope, and complexity of restoration programs is increasing. Although the importance of natural science to the success of such projects generally is recognized, the actual use of natural science in these programs rarely has been evaluated. We used techniques of program evaluation to examine the use of natural science in six American and three Western European regional-scale restoration programs. Our results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…The legacy of shoreline change throughout the Pacific Northwest catalyzed a rich body of research on large-scale coastal restoration with relevance to coastal cities globally [113][114][115][116][117]. Current evolutions in ecological science and guidance continue to have relevance to marinas and other marine related built environments, in particular: (a) comparative studies of biodiversity and community assemblage on built versus natural substrates [118][119][120], (b) roles of invasive species on built structures [121], and (c) emerging studies on ecological influences of marine energy installations [122,8].…”
Section: Developments In Marine Ecological Guidancementioning
confidence: 99%
“…The legacy of shoreline change throughout the Pacific Northwest catalyzed a rich body of research on large-scale coastal restoration with relevance to coastal cities globally [113][114][115][116][117]. Current evolutions in ecological science and guidance continue to have relevance to marinas and other marine related built environments, in particular: (a) comparative studies of biodiversity and community assemblage on built versus natural substrates [118][119][120], (b) roles of invasive species on built structures [121], and (c) emerging studies on ecological influences of marine energy installations [122,8].…”
Section: Developments In Marine Ecological Guidancementioning
confidence: 99%
“…Van Cleve et al (2006) reviewed several large regional-scale restoration projects to evaluate the influence of natural science in coastal restoration ( Figure 4). They analyzed how restora tion efforts integrate science into the organizational structure and assess if adequate organization would dictate the effective use of science.…”
Section: Restoration and Rehabilitation: Why Semantics Matter When Admentioning
confidence: 99%
“…Using techniques of program evaluation to analyze the use of natural science, Van Cleve et al (2006) found that the use of science can be con strained by the absence of formal, integrated mechanisms for including science into program execution. One of their major findings is the different perception of the word 'restoration' in Europe where returning a system to a 'pristine' condition is considered neither possible nor desirable.…”
Section: Restoration and Rehabilitation: Why Semantics Matter When Admentioning
confidence: 99%
“…state will be a best guess, subjective or valued judgement [17]. Fonseca et al (2002) [18] make the further distinction between compensatory restoration and primary restoration.…”
Section: Ii4 Rehabilitation Vs Restorationmentioning
confidence: 99%